2016
DOI: 10.1016/j.jplph.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic screening of Arabidopsis T-DNA insertion lines for cell wall mechanical properties revealed ANTHOCYANINLESS2, a cell wall-related gene

Abstract: We performed a phenotypic screening of confirmed homozygous T-DNA insertion lines in Arabidopsis for cell wall extensibility, in an attempt to identify genes involved in the regulation of cell wall mechanical properties. Seedlings of each line were cultivated and the cell wall extensibility of their hypocotyls was measured with a tensile tester. Hypocotyls of lines with known cell wall-related genes showed higher or lower extensibility than those of the wild-type at high frequency, indicating that the protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…S7 A ). SlANL2b (Solyc06g035940.2) is paralogous to CD2 ( CUTIN DEFICIENT 2 ), a regulator of epidermal cell cuticle deposition ( 38 ) whose orthologous A. thaliana loss-of-function mutant increased cell wall polysaccharide content ( 39 ). Solyc03g120910.2 is orthologous to an A. thaliana gene involved in vascular development and parenchyma pith cell primary wall retention ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…S7 A ). SlANL2b (Solyc06g035940.2) is paralogous to CD2 ( CUTIN DEFICIENT 2 ), a regulator of epidermal cell cuticle deposition ( 38 ) whose orthologous A. thaliana loss-of-function mutant increased cell wall polysaccharide content ( 39 ). Solyc03g120910.2 is orthologous to an A. thaliana gene involved in vascular development and parenchyma pith cell primary wall retention ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was shown that ROC4 is involved in the regulation of genes involved in cell wall precursor metabolism and by consequence in the specification of outer cell layers such as epidermis, exodermis, and sclerenchyma (Huang et al., 2012; Ito et al., 2003). Its closest homologs in Arabidopsis, HOMEODOMAIN GLABROUS1 ( HDG1 , At3g61150 ) and ANTHOCYANINLESS2 ( ANL2 , At4g00730 ), are involved in lateral root development and in meristem cell proliferation and root radial patterning (Horstman et al., 2015; Kubo et al., 1999; Kubo & Hayashi, 2011; Mabuchi et al., 2016; Nakamura et al., 2006). Altogether, the data suggest that ROC4 is likely involved in crown root primordia formation downstream of CRL1.…”
Section: Discussionmentioning
confidence: 99%
“…As explained above, the gene CD2/ANL2 was strongly upregulated in both StNAC103 transgenic lines in agreement with the increase of suberin and wax compounds. It has been reported that CD2/ANL2 is a class IV homeodomain Leucine zipper (HD-ZIP IV) whose mutation in addition to the effects in cutin and waxes, gives rise to an increase in cuticle water permeability [51,57] and also lower cell wall extensibility [58]. ALCATRAZ is a basic helix loop helix (bHLH) transcription factor involved in fruit dehiscence by promoting cell differentiation [59] and was also upregulated in both NAC silencing lines.…”
Section: Discussionmentioning
confidence: 99%